Interactive Exhibition on Climate Geoengineering: Empowering Future Teachers for Sociopolitical Action - Linhares, Elisabete Fernandes (2017)
Abstract The present case study, involving 19 pre-service teachers, intends to identify the potentialities and the limitations associated with the development of interactive exhibitions on socio-scientific issues as a strategy to empower future teachers for sociopolitical action. An interactive scientific exhibition developed accordingly to the IRRESISTIBLE project module "Geoengineering: Climate Control?" sought to create opportunities for students to work collaboratively, to take responsibility and to participate in activism initiatives. The results suggest positive impacts on students’ scientific knowledge, exhibitions’ development skills and empowerment for action. The main difficulties are focused on group work and time management. This pedagogical initiative allowed the development of competences considered important for citizens’ scientific literacy and active involvement in sociopolitical action. Resumo O presente estudo de caso, envolvendo 19 estudantes da formação inicial de professores, pretende identificar as potencialidades e as limitações associadas ao desenvolvimento de exposições interativas sobre questões sociocientíficas como estratégia para capacitar as futuras professoras para a ação sociopolítica. Uma exposição científica interativa desenvolvida de acordo com o módulo "Geoengenharia: Controlo do Clima?" do projeto IRRESISTIBLE procurou criar oportunidades para as estudantes trabalharem de forma colaborativa, assumirem responsabilidades e participarem em iniciativas de ativismo. Os resultados sugerem impactos positivos no conhecimento científico, em competências para o desenvolvimento de exposições e de capacitação para ação das futuras professoras. As principais dificuldades centram-se no trabalho de grupo e na gestão do tempo. Esta iniciativa pedagógica permitiu o desenvolvimento de competências consideradas importantes para a literacia científica dos cidadãos e o envolvimento ativo em ação sociopolítica.